Multi-instrument characterization of optical turbulence at the Ali observatory. (March 2015) - Liu, L-Y; Yao, Y-Q; Vernin, J; Wang, H-S; Yin, J; Qian, X
Abstract: In order to characterize the atmospheric optical turbulence at Ali observatory, we have deployed multi-instruments, which are able to continuously monitor the optical turbulence for site evaluation. These instruments include the DIMM, MASS, Single Star SCIDAR and Polaris seeing monitor, and we also plan to install SNODAR and Micro-thermal sensors for the turbulence on surface layer by the end of this year. This configuration allows us to collect a substantial database and make cross-comparison of the results. We have successfully obtained the profiles of optical turbulence and wind speed with Single Star SCIDAR, as well as the key parameters for adaptive optics application, such as seeing, coherence time, and isoplanatic angle. The DIMM seeing measurements are also carried out simultaneously. The median seeing measured by the DIMM and SSS in 2013 is 0.69 and 0.79 arcsec, respectively.